Counseling Teachers' Efforts In Implementing Student Career Exploration - Meivani, Dara; S, Irwan; Syarqawi, Ahmad (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
The purpose of this research is to know or explain the career exploration of students at MTs Darul Ulum Budi Agung Medan. This research uses a descriptive research method or a phenomenological approach. Procedures that produce descriptive data in the form of written or spoken words from people and observed behavior. The subjects of this study were the school principals, counseling teachers and the students it self. The efforts made by counseling guidance teachers by carrying out group guidance. The results of this study will indicate the efforts of guidance and counseling teachers in implementing student career exploration, namely by carrying out guidance and counseling services, namely group guidance.